Case report: First case of undifferentiated embryonal sarcoma of the liver in a child with neurofibromatosis type 1, treated by hepatic chemoperfusion with transcatheter arterial chemoembolization - Sinichenkova, Ksenia; Yasko, Ludmila; Akhaladze, Dmitry; Petrushin, Anton; Konovalov, Dmitry; Abasov, Ruslan; Mareeva, Yulia; Melekhina, Olga; Usman, Natalia; Karachunsky, Alexander; Novichkova, Galina; Litvinov, Dmitry; et al. (Frontiers in Oncology, 2022)
Introduction: In this report we firstly describe undifferentiated embryonal sarcoma of the liver (UESL) in a patient with neurofibromatosis type 1 (NF1), fatally complicated by synchronous malignant peripheral nerve sheath tumor (MPNST) with a highly aggressive metastatic course. The case also represents our first experience of chemoperfusion involving the transcatheter arterial chemoembolization (TACE) in a pediatric patient, applied as a treatment for UESL. Case presentation: A 13-year-old girl was diagnosed with NF1 and presented with a liver tumor identified as UESL by histological assessment. The tumor was refractive to the conventional first-line chemotherapy. The patient received hepatic chemoperfusion with TACE, which was efficacious; however, the overall curative outcome was unsatisfactory due to synchronous unresectable retroperitoneal MPNST with mesenteric metastases and ultimate progression of the UESL. Conclusion: This is the first reported case of UESL in a patient with NF1. The results demonstrate the efficacy of hepatic chemoperfusion with TACE in pediatric UESL.